Students with autism : characteristics and instructional programming for special educators - Clark, Claudia; Brady, Michael P.; Scott, Jack. (San Diego, CA : Singular, 2000)
This book is about: The nature of autism; Educational programming; Present and future contexts.
Keywords: Education; Austism; Autistic children; United States; Autistic children -- Education -- United States; Autism -- United States